Politik Hukum Pemilihan Kepala Daerah Langsung dan Serentak: Dinamika, Tantangan, dan Prospek Pembaharuannya - Gunardi SA Lumbantoruan (CV Rewang Rencang, 2024)
Direct and simultaneous Regional Head Elections (Pilkada), which are intended to create political stability and cost efficiency, may result a fragmented and less efficient government. This study shows that local elections in Indonesia have undergone significant developments, evolving from appointment system by the central government, to a direct and simultaneous election system. Nonetheless, Pilkada in Indonesia cannot be said to be concurrent local elections, because they are not held concurrently with the election of regional representatives.. Therefore, the implementation of Pilkada must be synchronized with the election of DPRD members in order to yield a concurrent and more efficient government.